2013
DOI: 10.5751/es-05875-180425
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Household Level Outcomes of Community Based Natural Resource Management: the Tchuma Tchato Project and Kwandu Conservancy

Abstract: ABSTRACT. Community based natural resource management (CBNRM) programs aim to link the achievement of conservation objectives with those of rural development and poverty alleviation. However, after more than a decade of implementation in southern Africa, there is remarkably little rigorous analysis of their achievements with respect to these goals. An evaluation of two CBNRM interventions, the Tchuma Tchato Project in Mozambique and the Kwandu Conservancy in Namibia, measured the impacts at the household level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…6). In some cases, the unequal distribution of benefits was due in part to the relatively scarce benefits available to members, such that only a small percentage of CBC members (e.g., those directly employed at the CBC) actually received any https://www.ecologyandsociety.org/vol23/iss3/art39/ benefits (e.g., Wainwright and Wehrmeyer 1998, Suich 2013, Silva and Mosimane 2014). Yet, elite capture, where local and extralocal elites received a disproportionate percentage of benefits and engaged in exclusionary membership practices, was a major factor in the unequal distribution of benefits within CBCs (e.g., Wainwright and Wehrmeyer 1998, Songorwa 1999, Collomb et al 2010, Hoole 2010, Kamoto et al 2013, Silva and Mosimane 2014, Silva and Motzer 2015.…”
Section: Social Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…6). In some cases, the unequal distribution of benefits was due in part to the relatively scarce benefits available to members, such that only a small percentage of CBC members (e.g., those directly employed at the CBC) actually received any https://www.ecologyandsociety.org/vol23/iss3/art39/ benefits (e.g., Wainwright and Wehrmeyer 1998, Suich 2013, Silva and Mosimane 2014). Yet, elite capture, where local and extralocal elites received a disproportionate percentage of benefits and engaged in exclusionary membership practices, was a major factor in the unequal distribution of benefits within CBCs (e.g., Wainwright and Wehrmeyer 1998, Songorwa 1999, Collomb et al 2010, Hoole 2010, Kamoto et al 2013, Silva and Mosimane 2014, Silva and Motzer 2015.…”
Section: Social Outcomesmentioning
confidence: 99%
“…Most cases that reported negative social outcomes also reported reductions in social capital. This occurred in the context of eroding community trust, changes to and reduction of traditional rules of use, and breakdowns in traditional networks and institutions (e.g., Songorwa 1999, Balint and Mashinya 2006, Jayne et al 2009, Kamoto et al 2013, Suich 2013, Dyer et al 2014, Silva and Motzer 2015. For instance, in Malawi, Forestry Assistants were hired by the Forestry Department to enforce the 1996 Forest Policy in local Village Forest Areas.…”
Section: Social Outcomesmentioning
confidence: 99%
“…The impact of CBNRM on income has been statistically insignificant for the average household (Pailler, Naidoo, Burgess, Freeman, & Fisher, 2015;Riehl, 2014;Suich, 2013), whereas improvements in health (Naidoo & Johnson, 2013;Riehl, 2014) and food security (Pailler et al, 2015) have been identified. The question therefore remains: Why are the impacts of CBNRM inconsistent?…”
mentioning
confidence: 99%
“…One possible reason is that particular livelihoods benefit more than others from CBNRM (Collomb et al, 2008;Scanlon & Kull, 2009;Suich, 2013). Looking primarily at the direct income and financial aspects while neglecting the indirect benefits from conservation may present another reason why impacts of NRM are conflicting (TEEB, 2012;WAVES, 2016).…”
mentioning
confidence: 99%
“…Namibia introduced the concept of Community Based Natural Resource Management (CBNRM) over the past decade to allow the involvement of local farmers in the management of natural resources including wildlife (Fabricius & Koch, 2004). The main emphasis of CBNRM is to ultimately give local people rights to management wildlife resources within their areas generating benefits for their livelihoods while at the same time ensuring continued survival of these resources CBNRM is founded on 4 pillars, namely sustainable conservation, economic development, devolution of rights and collective proprietorship (Suich, 2013). The success of the implementation of the CBNRM approach in Namibia has contributed to the increasing community led conservation areas which are currently serving as important corridors between different protected areas for wildlife.…”
Section: Introductionmentioning
confidence: 99%